Structure and function of a silicic acid channel Lsi1 - Saitoh, Yasunori; Suga, Michihiro (Frontiers in Plant Science, 2022)
Silicon is a beneficial element for plant growth and production, especially in rice. Plant roots take up silicon in the form of silicic acid. Silicic acid channels, which belong to the NIP subfamily of aquaporins, are responsible for silicic acid uptake. Accumulated experimental results have deepened our understanding of the silicic acid channel for its uptake mechanism, physiological function, localization, and other aspects. However, how the silicic acid channel efficiently and selectively permeates silicic acid remains to be elucidated. Recently reported crystal structures of the silicic acid channel enabled us to discuss the mechanism of silicic acid uptake by plant roots at an atomic level. In this mini-review, we focus on the crystal structures of the silicic acid channel and provide a detailed description of the structural determinants of silicic acid permeation and its transport mechanism, which are crucial for the rational creation of secure and sustainable crops.